Performance analysis of VC receiver systems for M2M communications using orthogonal frequency‐division multiple access. Issue 16 (1st November 2016) - Wang, Shendi; Thompson, John S.
Abstract : With increasing demand for machine‐to‐machine (M2M) communications, modifying existing orthogonal frequency‐division multiple access communication systems such as the long‐term evolution (LTE) system to successfully support low‐data rate M2M devices has become an important issue. In LTE Release 12 and beyond, the reduction of maximum bandwidth, the reduction of transmission power and the reduction of downlink transmission model should be studied for supporting low‐data rate M2M communications. This paper will address one solution based on the virtual carrier (VC) concept, which aims to improve the bandwidth efficiency and cost‐efficiency, using analogue filters to extract only sub‐carriers of interest. This will reduce the sampling rate at the M2M analogue‐to‐digital converter (ADC) leading to improvements in ADC power consumption and the computational complexity. Our results indicate that the VC system can provide significant high signal‐to‐interference‐plus‐noise ratio performance without significant bit error rate degradation.